NOBODY KNOWS: OPPRESSION AND RESISTANCE IN THE NARRATIVES OF FREDERICK DOUGLASS AND OLAUDAH EQUIANO - Cabral, Gladir da Silva (Revista Interfaces, 2020)
This article intends to analyze the autobiographic narratives by Frederick Douglass and Olaudah Equiano, two important slave narratives, Equiano was born free in Africa, was captured and fled from slavery to live in London; and Douglass was born in slavery, from African descendants. Equiano lived in the 18th century and Douglass in the 19th century. They lived a century apart. After a brief presentation and contextualization of the genre of slave narrative, I analyze the works selected, having as focus their critical content in relation to religion, economy, the legal system, and language. The analysis allowed me to understand how such cultural and social elements usually employed to oppress the slave were used as instrument confrontation of slavery and search for autonomy. Some of my theoretical references are: Henry Louis Gates Jr., Alex Argyros, Roger Rosemblatt, Edward Said, and Jacques Derrida.